Quantification of Endothelin-1 Gene Expression in the Diabetic Patients' Type II (DMT2) with Cardiovascular Disease - Mervat Kamil Kadhim, Alaa Mohammad Hasson Al-Husseini, (Pakistan Journal of Medical & Health Sciences, 2022)
The goal of this study is to see if there's a link between diabetes type 2 problems and endothelin-1 overexpression (ET-1). Where (90) blood samples from participants were obtained and divided into three groups: a first group representing individuals with (Hypertensive DMT2) and a second group representing (Hypertensive DMT2with CVD,), while the third group was represented by a control group. mRNA was extracted from blood samples then converted to cDNA by using the (qPCR) technique. When comparing the levels of ET-1 in the (hypertensive DMT2 and hypertensive DMT2with CVD groups ) to the control group, the results showed a significant difference (p<0.05), The current study analyzed the ET-1 gene in type 2 diabetes and cardiovascular disease, which could be a new target for early CVD therapy in the future. Keywords: endothelin-1gene, diabetes type II, cardiovascular disease, , endothelial dysfunction